Strangeness in the poetry of Muzaffar al-Nawab - المدرسة المساعدة النة شيروان (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
This article is a triggering point to poems of Mozafar Nawab which is written in pure Arabic. Mozafar Nawab is one of those poets which is known for his radical political attitude against Arabic regime. This attitude brought him deportation and alienation. This can be reason he lived and died vagrantly. In this article alienation as the most explicit and effective poetic concepts applied by poet has been detected. While searching Mozafar Nawab'poetic concepts , the effect of alienation has been traced which poet has used in his works. Meditation, sadness ,angriness and homesickness are the clearest tools for poet to express his internal emotions. As for Nawab's poems all kinds of alienation (home alienation, social alienation , mental alienation even spiritual alienation)has been collected.